Interregional Payments: Reply - Hartland, Penelope C. (Quarterly Journal of Economics, 1950)
Interregional Payments: Reply Penelope C. Hartland Penelope C. Hartland Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 3, August 1950, Pages 489–490, https://doi.org/10.2307/1884564 Published: 01 August 1950